2017
DOI: 10.1111/mec.14402
|View full text |Cite
|
Sign up to set email alerts
|

High rate of adaptive evolution in two widespread European pines

Abstract: Comparing related organisms with differing ecological requirements and evolutionary histories can shed light on the mechanisms and drivers underlying genetic adaptation. Here, by examining a common set of hundreds of loci, we compare patterns of nucleotide diversity and molecular adaptation of two European conifers (Scots pine and maritime pine) living in contrasted environments and characterized by distinct population genetic structure (low and clinal in Scots pine, high and ecotypic in maritime pine) and dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 121 publications
(214 reference statements)
4
29
2
Order By: Relevance
“…The neutral nucleotide diversity around 0.004 per bp found in this study is similar to what has been observed in previous studies of this species (Kujala & Savolainen, 2012) and in several other conifers (Eckert et al, 2013) (Brown, Gill, Kuntz, Langley, & Neale, 2004) (Grivet et al, 2017). Given the mostly continuous distribution of wind-pollinated P. sylvestris and the previous findings of near-absent population structure, only very negligible differences between populations were anticipated, with the exceptions of geographically isolated populations (Kujala & Savolainen, 2012;Pyhäjärvi et al, 2007;Wachowiak, Balk, & Savolainen, 2009).…”
Section: Indications Of Population Structuresupporting
confidence: 90%
“…The neutral nucleotide diversity around 0.004 per bp found in this study is similar to what has been observed in previous studies of this species (Kujala & Savolainen, 2012) and in several other conifers (Eckert et al, 2013) (Brown, Gill, Kuntz, Langley, & Neale, 2004) (Grivet et al, 2017). Given the mostly continuous distribution of wind-pollinated P. sylvestris and the previous findings of near-absent population structure, only very negligible differences between populations were anticipated, with the exceptions of geographically isolated populations (Kujala & Savolainen, 2012;Pyhäjärvi et al, 2007;Wachowiak, Balk, & Savolainen, 2009).…”
Section: Indications Of Population Structuresupporting
confidence: 90%
“…Overall, the H e per nucleotide for the assembled transcriptomes we assessed was lower than expected based on previous studies (Grivet et al, 2017), ranging from 1.2 x 10 -4 to 8.3 x 10 -4 (Table 2), an order of magnitude lower than previously reported in P. sylvestris ((Pyhäjärvi et al, 2011). The minimum required read depth and missing data threshold we applied to our data set were relatively lenient, which has probably increased the number of callable sites relative to variant calls.…”
Section: Influence Of Transcriptome Assembly Strategies On Estimates contrasting
confidence: 79%
“…We generated three vcf files per reference transcriptome according to the ploidy of the tissues: one vcf for the ME (haploid), one for the EM (diploid), and one combining NE+PH+VB (Tajima, 1989) per nucleotide was calculated for each transcript individually. Given that the expected value of π is equal to θ (=4N e μ ), we contrasted our observations to earlier, independent θ estimates for P. sylvestris (Grivet et al, 2017;Kujala & Savolainen, 2012;Pyhäjärvi et al, 2007;Pyhäjärvi, Kujala, & Savolainen, 2011…”
Section: Quality Assessment and Completeness Of Secondary Clustering mentioning
confidence: 99%
See 1 more Smart Citation
“…However, given increasing and recent evidence of pervasive effects of different types of selection across genic regions with HT data (e.g. Zhang Grivet et al 2017). Since Q. robur is the most pioneering species, it has likely been submitted to very strong environmental pressures at the time of stand establishment.…”
Section: Diversity Magnitude and Heterogeneity Highlight Species Intementioning
confidence: 99%